Rychlý pokles glomerulární filtrace zvyšuje u starších pacientů kardiovaskulární riziko - Shlipak, Michael G; Katz, Ronit; Kestenbaum, Bryan (Postgraduální nefrologie, 2009)
Chronic kidney disease (CKD), defined at a specific time point, is an important risk factor for cardiovascular disease. Whether the rate of kidney function decline contributes additional cardiovascular risk is unknown. In the Cardiovascular Health Study, we compared the associations of changes in kidney function during the first 7 yr with the incidence of heart failure (HF), myocardial infarction (MI), stroke, and peripheral arterial disease (PAD) during the subsequent 8 yr. We defined a rapid decline in cystatin C-based estimated GFR as >3 ml/min per 1.73 m(2)/yr, on the basis of determination at baseline, year 3, and year 7. Among eligible participants, 1083 (24%) had rapid kidney decline. The incidence of each type of cardiovascular event was significantly higher among patients with rapid decline (all P < 0.001). After multivariate adjustment for demographics, cardiovascular disease risk factors, and baseline kidney function, rapid kidney function decline was significantly associated with HF (adjusted hazard ratio [HR] 1.32; 95% confidence interval [CI] 1.13 to 1.53), MI (HR 1.48; 95% CI 1.21 to 1.83), and PAD (HR 1.67; 95% CI 1.02 to 2.75) but not with stroke (HR 1.19; 95% CI 0.97 to 1.45). The association of rapid decline with each outcome did not differ by the presence or absence of CKD. In conclusion, declining kidney function associates with higher risk for HF, MI, and PAD among patients with or without CKD
Keywords: Spojené státy americké; hodnoty glomerulární filtrace; lidé; kardiovaskulární nemoci; Financing, Organized; Cystatin C; financování organizované; Risk Factors; Heart Failure; Peripheral Vascular Diseases; Female; Stroke; srdeční selhání; Longitudinal Studies; cystatin C; infarkt myokardu; Humans; Myocardial Infarction; Renal Insufficiency, Chronic; cévní mozková příhoda; United States; onemocnění periferních cév; chronická renální insuficience; mužské pohlaví; Cardiovascular Diseases; Time Factors; ženské pohlaví; kreatinin; Aged, 80 and over; senioři nad 80 let; longitudinální studie; časové faktory; Aged; Male; Glomerular Filtration Rate; Creatinine; rizikové faktory; senioři